The CSR spillover effect on consumer responses to advertised reference price promotion - Chih-Huang Lin; Yuan-Shuh Lii; May-Ching Ding (Administrative Sciences, 2022)
This paper highlights the moderating effect of retailer CSR perception and CSR contribution type on the relationship between advertised reference price (ARP) and consumer evaluations. A two-by-three between-subjects factorial design is employed with the manipulation of ARP and CSR contribution type for hypothesis testing. Experimental results show that internal reference price, value of the deal, attitude towards the deal and purchase intention are higher for the exaggerated ARP than for the plausible ARP in the high CSR perception condition. Similar effects also occur when the retailer CSR contribution type is present in the reference price advertisement. Specifically, in-kind contribution exerts larger effects than money. This study contributes to a better understanding and crafting of integrative ARP and CSR strategies to influence consumers' price perceptions, evaluations and intentions.
Keywords: 350; corporate social responsibility; advertised reference price; construal level; contribution type